Buddhas and ancestors: religion and wealth in fourteenth-century Korea - Ahn, Juhn Young (Korean studies of the Henry M. Jackson School of International Studies, 2018)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Author's Note -- Koryŏ Kings and Reign Periods -- Introduction -- 1. Sowing the Seeds of Salvation with Wealth -- 2. Dark and Mysterious Ways -- 3. This Way of Ours -- 4. All the King's Men -- 5. Buddhas and Ancestors -- Conclusion -- Notes -- Glossary of Chinese Characters -- Bibliography -- Index.